Analisis Nilai Akidah dalam Novel Inna Ma’al Usri Yusra Karya Muhammad Makhdlori - Dian Permanasari; Nani Angraini (LPPM STKIP PGRI Bandar Lampung, 2023)
The novel Inna Ma'al Ausri Yusra is one of the novels that will be discussed more deeply related to the value of faith. The values of faith that will be studied are related to divine values, prophecy, ruhiyat, and samiyat. The method of this research is library research using descriptive analysis method. Based on the results of the analysis of the divine aspect, the author describes Fatimah's faith and piety who has experienced trials and tests. From the aspect of prophecy, the author describes it implicitly and explicitly in the story, about Fatima's determination to achieve high faith even though trials and suffering always befall her, she is guided by the story of the Prophet Muhammad. From the rihiyyat aspect, there is a belief in this value. Azwar is wrong. He believes in spirits. He uses his knowledge to manipulate his patients to comply with their wishes. From the sam'iyat aspect, it is illustrated in the story through the Koran, there are five letters consisting of five hadiths that support the arguments of the Koran so that the story has a strong legal basis.